2005
DOI: 10.1128/aac.49.5.1973-1980.2005
|View full text |Cite
|
Sign up to set email alerts
|

OXA-46, a New Class D β-Lactamase of Narrow Substrate Specificity Encoded by ablaVIM-1-Containing Integron from aPseudomonas aeruginosaClinical Isolate

Abstract: A novel OXA-type enzyme, named OXA-46, was found to be encoded by a gene cassette inserted into a class 1 integron from a multidrug-resistant Pseudomonas aeruginosa clinical isolate. The variable region of the integron also contained a bla VIM-1 metallo-␤-lactamase cassette and a duplicated aacA4 aminoglycoside acetyltransferase cassette. OXA-46 belongs to the OXA-2 lineage of class D ␤-lactamases. It exhibits 78% sequence identity with OXA-2 and the highest similarity (around 92% identity) with another OXA-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…The structures of the variable regions of integrons carrying the bla VIM gene cassette were determined for strains PA66, AK5493, Ps100, PA555, 67MG, 85MG, 105MG, and 134MG (for the other strains, it had previously been determined) (12,20,31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of the variable regions of integrons carrying the bla VIM gene cassette were determined for strains PA66, AK5493, Ps100, PA555, 67MG, 85MG, 105MG, and 134MG (for the other strains, it had previously been determined) (12,20,31).…”
Section: Resultsmentioning
confidence: 99%
“…The P. aeruginosa strains investigated in this study are listed in Table 1. They included (i) two representatives of a VIM-1-producing dominant Italian clone spreading in different hospitals since 1997 (the index strain VR-143/97 and strain PPV97, which were epidemiologically unrelated to each other and slightly different by PFGE profiling and which carried bla VIM integrons with different structures) (12,31); (ii) four additional VIM-1-producing P. aeruginosa isolates from Italy (representative of those spreading more recently in a long-term care and rehabilitation facility in northern Italy [L. Pagani et al, unpublished results]); and (iii) four VIM-4-producing isolates from Greece (n ϭ 1), Sweden (n ϭ 1) (11), and Hungary (n ϭ 2) (20). In addition, a VIM-2-producing isolate from Sweden (AK5493), obtained from a Greek national patient who had recently been hospitalized in Greece, was also included in the comparison.…”
Section: Methodsmentioning
confidence: 99%
“…It hydrolyzes mostly penicillins, oxacillin, and narrow-spectrum cephalosporins. Interestingly, it is inactivated by tazobactam and carbapenems but exhibits low susceptibility to NaCl (57).…”
Section: Acquired Narrow-spectrum Class D ␤-Lactamasesmentioning
confidence: 99%
“…We have observed that this specific property is shared by other class D ␤-lactamases, such as those belonging to the OXA-10 subgroup (unpublished data). Also, the production of some OXAs whose activity is inhibited by clavulanate or tazobactam, such as OXA-12 from A. jandaei (139) and OXA-18, OXA-45, and OXA-46 from P. aeruginosa (57,118,153), may be identified by synergy tests using clavulanic acid-containing disks. However, the result of these synergy tests may be misinterpretated and the corresponding isolates may be considered to be class A ESBL producers.…”
Section: Detection Of Class D ␤-Lactamase Genesmentioning
confidence: 99%
“…More recently identified cassettes are associated with genes that mediate resistance to rifampin and quinolones and increasingly also with genes encoding extended-spectrum ␤-lactamases and carbapenemases (82,88,136,200,203,208,261,264). Transcriptional control of resistance gene expression in class 1 integrons.…”
Section: Modulation Of Resistance Gene Expression In Class 1 Integronsmentioning
confidence: 99%